2018
DOI: 10.1021/acs.iecr.7b04940
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Practical Considerations When Selecting Solvents for Use in Extractables Studies of Polymeric Contact Materials in Single-Use Systems Applied in the Production of Biopharmaceuticals

Abstract: Regulatory authorities require the biopharmaceutical industry to demonstrate that extractables that may migrate from production systems do not alter the safety, efficacy, potency, or purity of drug products. Extractables studies of polymeric materials used in production systems and in particular single-use systems are designed to show material safety and should support the users to perform risk-based toxicological assessment of leachables that could potentially enter into the final product under process condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The AOs were gamma irradiated without any matrices to avoid matrix interferences and to gain in detection sensitivity in comparison with other studies using plastics involving these additives. [24,55] Solutions of additives at 100 μg/mL were prepared in dichloromethane and spiked with an internal standard (2-fluorobiphenyl) at 20 μg/mL and subsequently injected in GC-MS. Solutions were prepared in duplicate and injections were done in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AOs were gamma irradiated without any matrices to avoid matrix interferences and to gain in detection sensitivity in comparison with other studies using plastics involving these additives. [24,55] Solutions of additives at 100 μg/mL were prepared in dichloromethane and spiked with an internal standard (2-fluorobiphenyl) at 20 μg/mL and subsequently injected in GC-MS. Solutions were prepared in duplicate and injections were done in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The velocity for reaching the maximum or equilibrium concentrations of the extractables depends on the diffusion process and on the diffusion-influencing parameters (i.e., time, temperature, and specimen geometry) in the polymer. [55] This urged us to work directly on the neat antioxidant by-products having a partition coefficient not so in disfavor of their accumulation in aqueous solution, that is to say, mostly <500-700 amu, which makes them detectable by gas chromatography coupled with mass spectrometry. Defining a comprehensive extractable profile of packaging materials requires the use of orthogonal state-of-the-art analytical methods and is beyond the scope of this study.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that although alcohol–water mixtures can have polarities in the semipolar to nonpolar range, these mixtures present several challenges in practical application. Extractions using alcohol–water mixtures can result in lower numbers or underestimated quantities of extractables compared to pure alcohol solvents . In addition, polymers may selectively absorb one component of the mixture, resulting in a change in the composition of the extraction solvent mixture and altered polarity.…”
Section: Extractionmentioning
confidence: 99%
“…They applied this approach to screen SUBs from different vendors and manufacturing dates to identify non‐satisfactory films. Lastly, Dorey et al () published an article that assessed the extractables of polymer materials, and showed that extractions with pure water, pure ethanol, and 1M solutions of NaOH and HCl were most appropriate to obtain the comprehensive profile of hydrophilic compounds, and avoided redundancies in compound detection. These authors used a mathematical approach to generate factors for polymer‐solvent interaction and determined experimentally how the solvents extracted eight different polymer materials for volatile, non‐volatile, and elemental compounds.…”
Section: Solvent Selections: Mass Spectrometry‐drivenmentioning
confidence: 99%
“…There are multiple sources of guidance (FDA, USP, as well as industry working groups such as PQRI and BPOG), for selection of solvent, pH, duration, and temperature (Jenke et al, ; Ding et al, , ; Norwood et al, , Guidance for industry: Container/closure systems for packaging human drugs and biologics chemistry, ; Wakankar et al, ). Beyond recommendation of solvent choice for extractions, recent literature shows the use of MS to guide extraction procedures and solvent selections (Dorey et al, ) in an effort to condense and unify the work. The Extractable and Leachables Safety Information Exchange (ELSIE) working group determined if a single extraction method with a limited number of solvents could be performed to reliably produce a comprehensive E&L profile.…”
Section: Solvent Selections: Mass Spectrometry‐drivenmentioning
confidence: 99%